Persistent and Emerging Organic Pollutants in the Marine Coastal Environment of the Gulf of Milazzo (Southern Italy): Human Health Risk Assessment - D’Agostino, Fabio; Bellante, Antonio; Quinci, Enza; Gherardi, Serena; Placenti, Francesco; Sabatino, Nadia; Buffa, Gaspare; Avellone, Giuseppe; Di Stefano, Vita; Del Core, Marianna (Frontiers in Environmental Science, 2020)
The Gulf of Milazzo (north-eastern Sicily) has been recognized as Italian Site of National Interest (SNI; areas characterized by high level of contamination with potential effects on human health) in 2005 because of its high level of pollution. In this study we measured the concentration of polycyclic aromatic hydrocarbons (PAHs), organochlorine pesticides (OCPs), and polyBrominated diphenyl ether (PBDE) in seawater and sediments sampled from the Gulf of Milazzo in order to assess (i) the environmental status of contamination, and (ii) cancer and non-cancer human health risk potentially due to dermal absorption from contaminated seawater and/or ingestion of contaminated fish. Particularly, POPs content in pelagic and demersal fish of different size classes (small, medium, and large) were estimated, starting from the measured seawater and sediments concentrations, using the KABAM model. In particular, Monte Carlo simulation techniques were applied to address uncertainty in assessment of the risk and to provide quantitative estimates of probability of exposition. Ingestion of contaminated pelagic and demersal fish was the dominant pathway of exposition with high probability of significant cancer risk (Ingestion Cancer Risk >10–4) and significant non-cancer risk (Hazard Index >1). No human health risks emerged to be associated to dermal adsorption from contaminated seawater. Benzo(a)pyrene show the highest Ingestion Cancer Risk with respect to the other PAHs, while the highest Hazard Index for non-cancerogenic molecules was estimated for the PBDE47 congener.